Detecting True Change in the Hospital Anxiety and Depression Scale, SF-36, and Hypothyroid Score when Monitoring Patients with Subclinical Hypothyroidism. Issue 3 (25th June 2019) - Karmisholt, Jesper; Andersen, Stig
Abstract : Guidelines suggest that subclinical hypothyroid (SCH) patients with thyrotropin (TSH) between 4 and 10 mU/L and symptoms associated with hypothyroidism should receive L-T4 substitution treatment, be evaluated, and continue treatment if symptoms subside. The latter requires detecting a true change in symptoms, which can be calculated from within-person variation in symptom evaluation tools. This led us to assess within-person variation in hypothyroid symptoms, in mood-related symptoms, and quality of life in patients with untreated SCH in order to support the recommended evaluations. Method: The within-person coefficient of variation (CV) was estimated from 13 consecutive monthly evaluations in 15 patients with initial TSH between 5 and 12 mU/L and no trend in TSH. Results: The within-person CV was rather large for the Hospital Anxiety and Depression Scale (HADS) and Zulewski hypothyroid score at 41.6 and 60.9%, respectively. For quality of life the within-person CV was lower at 8.0% for the physical component summary and 8.7% for the mental component summary from the SF-36 questionnaire. The difference required between two measurements to detect a true change was 97% for mood-related symptoms (HADS) and 140% for hypothyroid symptoms. For quality of life (SF-36) the required difference was 20%. Conclusion: Score differences of almost 100% and higher were required to support a true change in mood (HADS) and hypothyroid symptom scores in untreated SCH patients. For quality of life a true change was detected at a 20% difference in SF-36 scores. The hypothyroid score and HADS questionnaire do not seem useful for the evaluation of individuals.